2009
DOI: 10.1002/ardp.200900067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity Studies of New Cryptophycin Analogues

Abstract: Two analogues of cryptophycin were synthesized and biologically evaluated for their in-vitro cytotoxicities against several solid tumors and leukemia cell lines. The results revealed that both analogues exhibited a broad range of cytotoxic activity with observed IC(50 )values in the muM-range, and compound 4 was more effective than compound 3 in most assays studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…52 An improved method to access unit C precursors from b-azidopivalic acid (31) avoiding alkylating agents was introduced Scheme 2 Unit A precursor 14 synthesis using an enantioselective crotylboration. 42 recently. 32,34 31 can be synthesized in one step from cheap commercially available b-chloropivalic acid (30) in very high yields.…”
Section: Unit Cmentioning
confidence: 99%
“…52 An improved method to access unit C precursors from b-azidopivalic acid (31) avoiding alkylating agents was introduced Scheme 2 Unit A precursor 14 synthesis using an enantioselective crotylboration. 42 recently. 32,34 31 can be synthesized in one step from cheap commercially available b-chloropivalic acid (30) in very high yields.…”
Section: Unit Cmentioning
confidence: 99%
“…Two cryptophycin analogs with an elongated unit B fragment have been reported (Figure ) . The Arndt–Eistert reaction served as the key step in the synthesis of the corresponding homologated unit B building block, a β ‐amino acid.…”
Section: Cryptophycin Analogs and Sar Studiesmentioning
confidence: 99%
“…Cryptophycin analogs with an elongated unit B building block (IC 50 values in n m ) . Cell lines: K562, multidrug‐resistant human leukemia; LoVo, human colon carcinoma.…”
Section: Cryptophycin Analogs and Sar Studiesmentioning
confidence: 99%
“…However, due to the novel mechanism of action, other cryptophycin analogues are being investigated. Preliminary results show cytotoxic activity of two lactam analogues of cryptophycin 1 in the MDR human leukemia cell line K562 …”
Section: Drugs Able To Evade P‐glycoproteinmentioning
confidence: 99%
“…Preliminary results show cytotoxic activity of two lactam analogues of cryptophycin 1 in the MDR human leukemia cell line K562. 219 In addition, a hybrid structure in which one portion is characteristic of a cryptophycin and the other an epothilone named cryptothilone has been synthesized. The mechanism of action has not yet been clarified, but it has been shown that this compound has no affinity for either cryptophycin or the taxol/epothilone binding site on tubulin.…”
Section: Cryptophycinsmentioning
confidence: 99%